2021
DOI: 10.1016/j.ecolecon.2020.106810
|View full text |Cite|
|
Sign up to set email alerts
|

Extreme heat and stock market activity

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The behavioral paradigm, on the other hand, draws on the psychological literature dating back to the 1970s, which demonstrates that the weather affects human behavior 4. More importantly, for our purposes, investor sentiment―and thus financial markets―can be influenced by weather‐related factors such as sunshine and cloud coverage (Bassi et al., 2013; Hirshleifer & Shumway, 2003; Saunders, 1993), wind speed (Keef & Roush, 2002), humidity (Sariannidis et al., 2016), precipitation (Kaustia & Rantapuska, 2016) and air temperature (Bansal & Ochoa, 2011; Cao & Wei, 2005a; Floros, 2011; Keef & Roush, 2007; Peillex et al., 2021; Yan et al., 2022).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The behavioral paradigm, on the other hand, draws on the psychological literature dating back to the 1970s, which demonstrates that the weather affects human behavior 4. More importantly, for our purposes, investor sentiment―and thus financial markets―can be influenced by weather‐related factors such as sunshine and cloud coverage (Bassi et al., 2013; Hirshleifer & Shumway, 2003; Saunders, 1993), wind speed (Keef & Roush, 2002), humidity (Sariannidis et al., 2016), precipitation (Kaustia & Rantapuska, 2016) and air temperature (Bansal & Ochoa, 2011; Cao & Wei, 2005a; Floros, 2011; Keef & Roush, 2007; Peillex et al., 2021; Yan et al., 2022).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Kathiravan and Chinnadurai [13] selected three influencing factors including temperature, humidity, and wind speed, and found that different factors recorded a statistically significant influence on the returns of different indices. It was Peillex, Jonathan, et al [14] who observed the negative association between maximum daily temperatures and trading volumes by analyzing the trading volumes on the French stock market on days when the weather in Paris is excessively hot over the period 1995-2019.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the same vein, Donadelli, Jüppner, Paradiso, and Schlag (2021) argue that temperature‐volatility shocks undermine equity valuations and produce non‐negligible welfare costs. Peillex et al (2021) show that extreme heat above 300°C depresses stock‐market activity and, thereby, market returns (Hou et al, 2019). In general, the results of these significant research efforts indicate that climate risk tends to reduce productivity and/or the stochastic depreciation rate of capital, and also affects investors' propensity to trade via its implications for distraction, mood, etc., to produce an adverse impact on macroeconomic variables and equity valuations 1 .…”
Section: Introductionmentioning
confidence: 99%